Design and implementation of a GSM based weather station - Muchovo, Raphael (2018)
A wireless remote weather station is an ideal solution for knowing the weather conditions at a specific remote location. Weather forecasts are informative, but they are only a forecast. With a Remote Weather Station, one would always know the exact weather conditions from where ever the Remote Weather Station is located. This project seeks to devise a simple low cost microcontroller based remote weather station that measure weather conditions using sensors to measure temperature, humidity, atmospheric pressure, rainfall received, and light intensity, displays it on LCD and forwards it to a remote user by SMS. This project is developed by using Arduino uno, SIM900 GPRS/GSM shield, LCD display, temperature, humidity, atmospheric pressure and light intensity sensors. The advantage of using GSM based technology is that GSM based communication network is widespread in Zimbabwe and have almost reached every corner of the country. GSM technology also provides users with high quality signal and channels, giving them access to high quality digital communication at very affordable rates. This microcontroller based weather station can be useful to anyone who wishes to monitor the weather conditions of a location without being physically there.